Pedophilia and sexual offending against children : theory, assessment, and intervention - Seto, Michael C. (American Psychological Association, 2018)
This authoritative and comprehensive second edition summarizes and integrates advances in assessing and treating pedophilia and preventing sexual offending against children. It synthesizes current research and offers evidence-based recommendations for practice and policy reform.